The Development for Quality of Service for Division of Public Health and Environment in Bang Sai District, Phranakhon Si Ayutthaya Province - Ennoi, Pornmanat; Anusonphat, Nalaumon (Journal of Human and Society, Sisaket Rajabhat University, 2023)
The purposes of this research were 1) to study the quality of services provided by Bang Sai Public Health and Environment Division in sub-district municipality; 2) to study guidelines for improving the quality of services of the Public Health and Environment Division in Bang Sai sub-district municipality. There were 2 steps in this research. The first step was to study the quality of service for division of public health and environment in Bang Sai sub-district municipality. The sample were 385 external customers in Bang Sai sub-district municipality, Bang Sai district, Phranakhon Si Ayutthaya province, with stratified random sampling. The instrument was a questionnaire. The reliability was 0.90. The statistics were analyzed by mean, standard deviation, one-way ANOVA, and LSD test. The second step was to study the guidelines on the development for quality of service for division of public health and environment in Bang Sai sub-district municipality, Bang Sai district, Phranakhon Si Ayutthayaprovince. The sample were 11 key informants including, deputy mayor of Bang Sai sub-district municipality, director in division of public health and environment in Bang Sai sub-district municipality, director in Tambon health promoting hospital, headman, and village headman, with purposive sampling. The instrument used for the study was an interview form. Thecontent analysis was conducted. The results of the research found as follows: 1) The quality of service for division of public health and environment in Bang Sai sub-district municipality, Bang Sai district, Phranakhon Si Ayutthaya province in overall, it is at the highest level. The aspect with the highest average value was reliability. and the side with the lowest average is in terms of confidence 2) The guidelines for improving the quality of services of the Public Health and Environment Division of Tambon Municipality Bon Bang Sai, Bang Sai District, Phra Nakhon Si Ayutthaya Province, including the service should be provided for the specified period of time. The service channels should be more and rapid. Should be ready to provide the service, there should be attentiveness and enthusiasm. The service should be provided by the useful knowledge and information. It should be realized by the highest benefits and the explicit legal rules and regulations.